Government and the enterprise since 1900 : the changing problem of efficiency - Tomlinson, Jim (Clarendon Press ; Oxford University Press, 1994)
This book surveys the industrial policy of British governments from the beginning of the century to the early 1990s, exploring the perennial concern of administrations of all complexions with high growth, low unemployment, and competitiveness. The analysis proceeds chronologically and focuses on the formation and implementation of policy according to the prevailing ideology of the party in power. Industrial policy is traced through times of war and recession, the building of the welfare state, growth and stagflation, economic liberalism and deindustrialization. Two case studies, of the cotton and car industries, are presented to illustrate the historical discussion.